2013
DOI: 10.1111/1556-4029.12141
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analyte‐Probed Nanoextraction Coupled to Nanospray Ionization–Mass Spectrometry of Drug Residues from Latent Fingerprints

Abstract: Here, we present a method of extracting drug residues from fingerprints via Direct Analyte-Probed Nanoextraction coupled to nanospray ionization-mass spectrometry (DAPNe-NSI-MS). This instrumental technique provides higher selectivity and lower detection limits over current methods, greatly reducing sample preparation, and does not compromise the integrity of latent fingerprints. This coupled to Raman microscopy is an advantageous supplement for location and identification of trace particles. DAPNe uses a nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…We have developed a nanomanipulation workstation capable of collecting trace particles [10][11][12][13], single cells, and subcellular organelles [5,14,15]. The workstation can be equipped with up to four piezoelectric nanopositioners capable of simultaneously utilizing different end effectors, including microgrippers, nanospray emitters, and microelectrodes that perform low impedance electrical characterizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have developed a nanomanipulation workstation capable of collecting trace particles [10][11][12][13], single cells, and subcellular organelles [5,14,15]. The workstation can be equipped with up to four piezoelectric nanopositioners capable of simultaneously utilizing different end effectors, including microgrippers, nanospray emitters, and microelectrodes that perform low impedance electrical characterizations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that the nanomanipulator can be used as a surface-probing technique, direct analyte-probed nanoextraction (DAPNe), to extract drug residue from latent fingerprints [10], individual fibers [13], and trace explosive materials [12], in combination with direct analysis in real time mass spectrometry (DART-MS) [11]. DAPNe has also been utilized for the analysis of document inks, demonstrating the ability to characterize the chemistry of both antique and modern documents without interfering with the integrity of the document [17].…”
Section: Introductionmentioning
confidence: 99%
“…Direct analyte-probed nanoextraction (DAPNe) manages to alleviate the primary issues that arise with other sampling methods, including matrix effects and sample destruction [30][31][32]. Traditionally coupled to nanospray ionization-mass spectrometry (NSI-MS), this technique has displayed its value in trace analysis with extraction of illicit drugs from fibers [30], electrostatic lifts [31], and within fingerprints [32].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally coupled to nanospray ionization-mass spectrometry (NSI-MS), this technique has displayed its value in trace analysis with extraction of illicit drugs from fibers [30], electrostatic lifts [31], and within fingerprints [32]. Using a nanomanipulator mounted to the stage of a bright-field microscope, a capillary tip with a conductive coating can be directed to a particle of interest with 5 nm translational resolution [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation